The ntrBC genes of Rhizobium leguminosarum are part of a complex operon subject to negative regulation - Patriarca, E J; Riccio, A; Taté, R; Colonna-Romano, S; Iaccarino, M; Defez, R (Molecular microbiology, 1993)
We report here that ntrB and ntrC genes of Rhizobium leguminosarum biovar phaseoli are cotranscribed with an open reading frame (called ORF1) of unknown function. The promoter region of the ORF1-ntrB-ntrC operon was mapped immediately upstream of ORF1 and two in vivo transcription initiation sites were identified, both preceded by -35/-10 promoter consensus sequences. Some major aspects differentiate R. leguminosarum from the enteric nitrogen regulatory system: the ntrBC genes are cotranscribed with ORF1 which is homologous to an ORF located upstream of ntrBC of R. capsulatus and to the ORF1 located upstream of the fis gene of Escherichia coli; ntrBC are not transcribed from a -24/-12 promoter and are only autogenously repressed. Moreover, the intracellular concentration of the NtrC protein increases when the bacterium is grown on ammonium salts, while under the same conditions the promoter of one of its target genes, glnII, is 12 times less active.